Genomic Approaches for Improvement of Understudied Grasses - Keenan Amundsen (Frontiers Research Topics, 2017)
Grasses are diverse, spanning native prairies to high-yielding grain cropping systems. They are valued for their beauty and useful for soil stabilization, pollution mitigation, biofuel production, nutritional value, and forage quality; grasses encompass the most important grain crops in the world. There are thousands of distinct grass species and many have promiscuous hybridization patterns, blurring species boundaries. Resources for advancing the science and knowledgebase of individual grass species or their unique characteristics varies, often proportional to their perceived value to society. For many grasses, limited genetic information hinders research progress. Presented in this research topic is a brief snapshot of creative efforts to apply modern genomics research methodologies to the study of several minor grass species.